Ana Rosado Cubero: Barriers to Competition: The Evolution of the Debate (Perspectives in Economic and Social History). Londres, Pickering & Chatto, 2009, 230 págs. - Zabalza Aribuzu, Juan (Investigaciones de Historia Económica, 2019)
Sin resumen